Bis(cyano)iron(III) Porphyrinates: What is the Ground State? - Li, Jianfeng (Inorg Chem, 2015)
The synthesis of six new bis(cyano) iron(III) porphyrinate derivatives is reported. The anionic porphyrin complexes utilized tetraphenylporphyrin, tetramesitylporphyrin, and tetratolylporphyrin as the porphyrin ligand. The potassium salts of Kryptofix-222 and 18-C-6 were used as the cations. These complexes have been characterized by X-ray structure analysis, solid-state Mössbauer spectroscopy, and EPR spectroscopy, both in frozen CH(2)Cl(2) solution and the microcrystalline state. These data show that these anionic complexes can exist in either the (d(xz),d(yz))(4)(d(xy))(1) or (d(xy))(2)(d(xz),d(yz))(3) electronic configuration and some can clearly readily interconvert. This is a reflection that these two states can be very close in energy. In addition to the effects of varying the porphyrin ligand, subtle effects of the cyanide ligand environment in the solid-state and in solution are sufficient to shift the balance between the two electronic states.